TELAAH SOSIOLOGIS TERHADAP PENOLAKAN KOMERSIALISASI AGAMA DAN FEODALISME DI DESA KENJO, BANYUWANGI - Marta Putri Ameliana; Farid Pibadi (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study explores the socio-religious phenomenon of kyai (Islamic clerics) in Kenjo Village, Banyuwangi, who uphold the values of sincerity and reject both the commercialization of religion and feudal religious structures. In the context of modern society, religion is often used as an economic instrument or a symbol of social status. However, the kyai in Kenjo demonstrate a form of value rationality as proposed by Max Weber social actions driven by moral and spiritual beliefs rather than material gain. This research employs a descriptive qualitative approach through observation, interviews, and literature review. The findings reveal that kyai in Kenjo carry out their religious duties with simplicity, refusing financial rewards as a moral expression of sincerity. They also resist hierarchical religious relations by fostering egalitarian interactions with the community. Such behavior reflects the manifestation of religion as a lived social practice rather than merely a normative belief system. Hence, the role of kyai in Kenjo can be interpreted as a form of resistance against the commodification of religion and symbolic domination, embodying social actions oriented toward moral and spiritual values.